An Inuit Based Policy Development Process - Dunning, Norma (Alberta Journal of Educational Research, 2018)
This paper explores the use of Inuit Quajimajatuqangit (IQ) and the policy formation process of the rational decision making model. Based on the current research of Inuit Canadians concerning parental involvement within northern schools, this paper examines how an Indigenous way of knowing can be infused with a non-Indigenous method of policy development. The majority of this paper reviews past policy that has been placed upon Inuit Canadians as the framework for understanding how Inuit arrived at the current educational situation. The author introduces how Inuit have taken up this situation, and are working in present day with a positive perspective. Keywords: Inuit Quajimajatuqangit (IQ), Pijitsirniq, Aajiiqatigiingniq, Pilirqatigiingniq. Inuit Quajimajatuqangit (IQ) is Inuit knowledge and societal values through which Inuit function. Pijitsirniq is the concept of serving. Aajiiqatigiingniq is consensus in decision making. Pilirqatigiingniq is working together for a common purpose. Cet article explore l’emploi de l’Inuit Quajimajatuqangit et le processus d’élaboration des politiques du modèle de prise de décision rationnelle. Reposant sur la recherche actuelle par des Inuits canadiens sur l’implication des parents dans les écoles du Nord, cet article examine la mesure dans laquelle un mode autochtone de connaissance peut être empreint d’une méthode non autochtone d’élaboration des politiques. La majorité de l’article passe en revue les anciennes politiques imposées aux Inuits Canadiens; ce passé sert de cadre pour comprendre comment les Inuits en sont arrivés à la situation actuelle en matière d’éducation. L’auteure explique que les Inuits ont assumé cette situation et qu’ils y travaillent actuellement avec optimisme. Mots clés : l’Inuit Quajimajatuqangit (IQ), Pijitsirniq, Aajiiqatigiingniq, Pilirqatigiingniq. L’Inuit Quajimajatuqangit (IQ), ce sont les connaissances et les valeurs sociales avec lesquelles fonctionnent les Inuits. Pijitsirniq, c’est le concept du service. Aajiiqatigiingniq désigne le consensus dans la prise de décision. Pilirqatigiingniq, c’est travailler ensemble en vue d’atteindre un objectif commun.